Assessment of Prevalence of Malocclusion and Orthodontic Treatment Need in Young Population - Nidhi Ravindran; C B Moushmi (Asian Journal of Medical Research, 2019)
Background: Prevalence of malocclusion and orthodontic treatment need. Subjects & Methods: Five hundred eighty subjects of age range14-17 years of either gender was examined for orthodontic treatment need with Dental Health Component (DHC) of the Index of OrthodonticTreatment Need (IOTN). Treatment needs of the subjects were categorized as grade 1 (no treatment need), grade 2 (mild need), grade 3 (moderateneed), grade 4 (severe need), and grade 5 (extreme need). Results: IOTN index shows that grade 1 was seen among 22% males and 25% females,grade 2 in 45% males and 42% females, grade 3 in 24% males and 27% females, grade 4 in 5% males and 4% females and grade 5 in 4%males and 2% females. A significant difference was observed in class I, II and III malocclusion, overjet >4mm, cross bite, crowding, TMD anddiastema in both genders (P< 0.05). Conclusion: Most of the subjects had no orthodontic abnormality. Orthodontic treatment needs among studypopulation was lower.